2004
DOI: 10.1038/sj.sc.3101624
|View full text |Cite
|
Sign up to set email alerts
|

An unusual use of AMS 800 artificial urinary sphincter cuff in the treatment of sphincteric neurogenic incontinence: case report

Abstract: ) artificial urinary sphincter cuff in a female patient affected by neurogenic urinary incontinence. Objective: To describe this rare surgical solution. Setting: Department of Urology in Italy. Methods: A 43-year-old woman affected by flaccid paraplegia, acontractile bladder and incompetent bladder neck, underwent an implantation of an artificial urinary sphincter AMS 800. After 7 years, a mechanical failure of the device occurred and pubovaginal sling (PVS) utilizing the cuff of the sphincter was employed due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Siracusano et al [14] reported that in some patients with neurogenic sphincteric incontinence, an AUS can be considered as a treatment option. In pediatric urology, research about the outcome of bladder outlet procedures on children with urinary incontinence with neuropathic bladder dysfunction or structural deficiency is also rare.…”
Section: Discussionmentioning
confidence: 99%
“…Siracusano et al [14] reported that in some patients with neurogenic sphincteric incontinence, an AUS can be considered as a treatment option. In pediatric urology, research about the outcome of bladder outlet procedures on children with urinary incontinence with neuropathic bladder dysfunction or structural deficiency is also rare.…”
Section: Discussionmentioning
confidence: 99%